The protestant fiscal ethic: Religious confession and euro skepticism in Germany - Adrian Chadi; Matthias Krapf (University of Trier, Institute for Labour Law and Industrial Relations in the European Union (IAAEU), 2015)
During the European sovereign debt crisis, most countries that ran into fiscal trouble had Catholic majorities, whereas countries with Protestant majorities were able to avoid fiscal problems. Survey data show that, within Germany, views on the euro differ between Protestants and Non-Protestants, too. Among Protestants, concerns about the euro have, compared to Non-Protestants, increased during the crisis, and significantly reduce their subjective wellbeing only. We use the timing of survey interviews and news events in 2011 to account for the endogeneity of euro concerns. Emphasis on moral hazard concerns in Protestant theology may, thus, still shape economic preferences.
Keywords: E00; I31; L82; Z12; 330; protestantism; euro crisis; subjective wellbeing; media coverage